Deep evolutionary conservation of a sex-determining locus without sequence homology - Chuanxin Yu; Dean Hodapp; Safira Moog; Simon Dupont; Eric Darrouzet; Claudia Isabelle Keller Valsecchi; Thomas Joseph Colgan; Qiaowei Pan; Hugo Darras (Proceedings of the National Academy of Sciences, 2026)
Sex determination is fundamental to eukaryotic life, yet its molecular basis varies widely across the tree of life. In most animal clades, sex-determining mechanisms are highly diverse and evolve rapidly. Here, we identify an exception in aculeate Hymenoptera, an ancient and diverse clade of haplodiploid insects that includes ants, bees, and stinging wasps. By integrating comparative genomics across Hymenoptera with genetic mapping in bumblebees and hornets, we reveal that the ANTSR locus, a multiallelic noncoding locus, has been maintained for over 150 My as the primary instructive signal for female development. This locus is located in a conserved synteny block that originated at the base of Aculeata and functions as a highly polymorphic, zygosity-based sex determiner, with only heterozygous individuals developing as females across lineages. Despite its deep evolutionary conservation, this sex locus shows no detectable sequence homology among lineages. These findings demonstrate that an essential noncoding locus can retain its function over deep evolutionary time without sequence conservation. More broadly, our results highlight haplodiploid insects as a powerful model for studying the evolution of sex determination mechanisms beyond those linked to sex chromosomes.